2013
DOI: 10.5433/1679-0359.2013v34n5p2403
|View full text |Cite
|
Sign up to set email alerts
|

Valores energéticos de diferentes cultivares de milho para aves

Abstract: ResumoDevido ao alto custo que a alimentação representa na produção avícola, torna-se necessário o conhecimento da composição química e energética dos alimentos para formular rações precisas, objetivando melhor desempenho zootécnico e econômico da atividade. Desta forma, o objetivo deste trabalho foi determinar a composição química, os valores energéticos e os coeficientes de metabolizabilidade de diferentes cultivares de milho para aves. Para determinar os valores energéticos foi utilizado o método de coleta … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
6
1
2
Order By: Relevance
“…The AME and AME n differed (P < 0.05) among treatments, ranging from 2909 to 3246 kcal kg −1 and 2877 to 3239 kcal kg −1 (Table 5), respectively. The values were lower than those found by Henz et al (2013) in five corn cultivars under organic fertilization for 21-day-old broilers, of 3113 to 3325 kcal kg −1 for AME and 3059 to 3287 kcal kg −1 for AME n .…”
Section: Chemical Composition Energy Values and Metabolizable Coefficontrasting
confidence: 69%
“…The AME and AME n differed (P < 0.05) among treatments, ranging from 2909 to 3246 kcal kg −1 and 2877 to 3239 kcal kg −1 (Table 5), respectively. The values were lower than those found by Henz et al (2013) in five corn cultivars under organic fertilization for 21-day-old broilers, of 3113 to 3325 kcal kg −1 for AME and 3059 to 3287 kcal kg −1 for AME n .…”
Section: Chemical Composition Energy Values and Metabolizable Coefficontrasting
confidence: 69%
“…In this regard, Henz et al (2013) reported that the moisture content of grains is considered an important parameter, because in high humidity conditions and long-term storage, as well as high environmental temperature, fungi contamination can occur, which produce mycotoxins that causes metabolic disorders in animals. The lowest CP obtained (6.85%) was lower than those presented by the National Research Council -NRC (2012) and Rostagno et al (2011).…”
Section: Resultsmentioning
confidence: 99%
“…The high costs of feeding broiler chickens has aroused interest in new alternative sources of food, which can partially replace energy and protein foods in the diet, aiming at minimizing the costs of nutrition and, consequently, production (FREITAS et al, 2017;HENZ et al, 2013;SILVA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%